2021
DOI: 10.1093/europace/euab110
|View full text |Cite
|
Sign up to set email alerts
|

Impact of closed loop stimulation on prognostic cardiopulmonary variables in patients with chronic heart failure and severe chronotropic incompetence: a pilot, randomized, crossover study

Abstract: Aims Clinical effects of rate-adaptive pacing in heart failure patients with chronotropic incompetence (CI) undergoing cardiac resynchronization therapy (CRT) remain unclear. Closed loop stimulation (CLS) is a new rate-adaptive sensor in CRT devices. We evaluated the effectiveness of CLS in CRT patients with severe CI, focusing primarily on key prognostic variables assessed by cardiopulmonary exercise (CPX) testing. Methods and results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Previous studies in heart failure patients undergoing CRT and CI have shown that the CLS mode can improve VE/VCO 2 and the QoL. 7 , 15 , 16 Notably, patients with CRT with improved ejection fraction were more likely to respond positively to CLS-based rate-adaptive pacing, whereas those with reduced ejection fraction were less likely to respond. 7 , 16 …”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous studies in heart failure patients undergoing CRT and CI have shown that the CLS mode can improve VE/VCO 2 and the QoL. 7 , 15 , 16 Notably, patients with CRT with improved ejection fraction were more likely to respond positively to CLS-based rate-adaptive pacing, whereas those with reduced ejection fraction were less likely to respond. 7 , 16 …”
Section: Discussionmentioning
confidence: 95%
“…In accordance with criteria chosen based on previous studies, CI was defined as a maximum HR < 75% of the age-predicted maximum HR (APMHR = 220—age, applicable to healthy populations) during the exercise test. 7 , 9 , 12 Patients who did not meet the criteria for CI were subsequently excluded from further participation in the study.…”
Section: Methodsmentioning
confidence: 99%
“…The current state of knowledge on the use and optimization of the function of frequency adaptation in pacemakers is insufficient due to the small number of studies available and the contradictory results that have been recorded [4][5][6][7][8][9]. Furthermore, specific recommendations in the guidelines of the European Society of Cardiology on cardiac pacing and cardiac resynchronization therapy are limited [2,3].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, specific recommendations in the guidelines of the European Society of Cardiology on cardiac pacing and cardiac resynchronization therapy are limited [2,3]. Many studies rely on the electrocardiographic treadmill exercise test as an objective method of assessment of physical performance and progress in cardiac rehabilitation or for optimization of settings of implantable devices and cardiac [7,12,13]. Therefore, this study will deepen the research on the impact of the rate response function on physical performance in a homogeneous group of patients and will reveal which patients would benefit the most from rate-adapted pacing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation